Bacterial population solitary waves can defeat rings of funnels. (27th March 2017) - Morris, Ryan J; Phan, Trung V; Black, Matthew; Lin, Ke-Chih; Kevrekidis, Ioannis G; Bos, Julia A; Austin, Robert H
Abstract: We have constructed a microfabricated circular corral for bacteria made of rings of concentric funnels which channel motile bacteria outwards via non-hydrodynamic interactions with the funnel walls. Initially bacteria do move rapidly outwards to the periphery of the corral. At the edge, nano-slits allow for the transport of nutrients into the device while keeping the bacteria from escaping. After a period of time in which the bacteria increase their cell density in this perimeter region, they are then able to defeat the physical constrains of the funnels by launching back-propagating collective waves. We present the basic data and some nonlinear modeling which can explain how bacterial population waves propagate through a physical funnel, and discuss possible biological implications.